Pengaruh Kepemimpinan Transformasional Kepala Madrasah terhadap Kinerja Guru di MI Ma’arif NU 01 Kalijaran Kecamatan Karanganyar Kabupaten Purbalingga - Zahroh Zahroh (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2021)
This study aims to reveal the influence of the transformational leadership of the madrasa head on teacher performance at MI Ma'arif NU 01 Kalijaran, Karanganyar District, Purbalingga Regency. This research is a quantitative research. The population and sample in this study were all teachers at MI Ma'arif NU 01 Kalijaran, Karanganyar District, Purbalingga Regency, totaling 8 people. Data collection used a questionnaire, and data analysis used a simple regression analysis technique. This study resulted in the conclusion that the Madrasah Principal's Transformational Leadership has a significant influence on Teacher Performance MI Ma'arif NU 01 Kalijaran, Karanganyar District, Purbalingga Regency, as evidenced by the value of Sig = 0.009 < α = 0.05. The value of the correlation coefficient (r2) = 0.705 or a contribution of 70.5%